Well, to solve for X, we have to simplify the equation, so, remember PEMDAS.
Parentheses
Exponents
Multiplication
Division
Addition
Subtraction
Start with parentheses, and, divide the -2 to each number in the parentheses.
-2 ( x + 1/3 ) + 9x = 4
-2 times x is -2x, and, -2 times 1/3 equals -2/3.
So, now, our equation should look like this:
-2x - 2/3 + 9x = 4
Now, we combine our like-terms, since both -2x and 9x have the variable x attached to them, we can combine them:
-2/3 + 7x = 4
Now, we do the opposite of subtraction to move -2/3 over to the 4, which, is addition:
-2/3 + 7x = 4
+2/3 +2/3
_____________
7x = 4 2/3
Now, we just divide by 7 on each side to solve for X:
7x = 4 2/3
÷7 ÷7
__________
X = 2/3
I hope this helps!